Bridging Regional Talent and Niche Events through Artificial Intelligence - Tivary, Disha; Kannan, Ashwin (Journal of Environmental Management and Tourism, 2026)
This study examines how digital dining in Bengaluru has evolved and how these shifts are influencing consumer behaviour and restaurant operations. The research uses secondary data from industry reports, academic studies, and market analyses on food delivery, digital payments, and restaurant technologies. A thematic review approach was applied to identify major trends shaping the digital dining ecosystem. Digital dining in Bengaluru has expanded rapidly due to smartphone use, convenience-driven consumers, and strong platform ecosystems. Restaurants increasingly adopt delivery platforms, digital menus, and data-driven tools. Key challenges include high aggregator commissions, operational pressure, and heavy dependency on platforms. The study offers a focused understanding of how technology is reshaping urban dining markets, using Bengaluru as a leading example of digital transformation in foodservice. Findings are based solely on secondary data and may not capture deeper behavioural nuances. Insights can guide restaurants in planning technology adoption and improving customer experience.